Marketing Effectiveness of Akropora Decorative Coral (Acropora Sp.) at PT. Agung Aquatic Marine, Badung Bali - Ridwan, Muhammad; Kasmi, Mauli; Abdullah; Ilyas; Septiani, Lisa (Hasanuddin University, 2023)
Coral reefs are marine biota that reproduce by budding and fertilization, making them natural resources aquarium consumers in Europe, America, and Asia are very interested in. Since Indonesia is the largest tropical nation producing sponges, there is an increasing need for imported products. Consequently, it may be inferred whether marketing can be carried out effectively as planned or targeted in accordance with the targets that the organization has established. This study uses descriptive qualitative analysis to investigate the marketing strategies and efficiency of Akropora decorative corals (Acropora sp) at PT. Agung Aquatic Marine in Badung, Bali. Additionally, PT. Agung Aquatic Marine's marketing efforts are deemed successful because the business's target may be met and ornamental coral sales keep rising each month. In addition, the marketing carried out by PT Agung Aquatic Marine is considered effective because the sale of ornamental corals continues to increase every month and can achieve the company's target.